Effects of Adding Different Dietary Levels of Raw Mung Bean (Phaseolus aereus) on Productive Performance and Egg Quality of Laying Hens - Hassan , Sherif M. (International Journal of Poultry Science, 2016)
The present study was conducted to evaluate the effect of adding different dietary levels of raw mung bean (0, 5, 10 and 15%) on productive performance and egg quality of laying hens. Two hundred forty 55-week old Hisex laying hens with similar body weight and egg production were randomly distributed among 4 treatments with 15 replicates with 4 hens per each replicate. Body weight gain, feed consumption, egg production, egg weight, egg mass, feed conversion ratio, egg shell weight, egg shell weight surface area, egg shell thickness, egg specific gravity, egg yolk color and Haugh unit were measured. Results showed that hens fed diets containing 10 and 15% mung bean showed higher egg mass than those fed control diet containing 0% mung bean. In contrast, hens fed diets containing 10 and 15% raw mung bean showed higher (worst) feed conversion ratio than those fed control diet containing 0% raw mung bean. On the other hand, hens fed diets containing 15% raw mung bean showed higher egg shell weight, egg shell weight surface area and egg yolk color than those fed diets containing 0, 5 and 10% raw mung bean. In addition, hens fed diets containing 15% raw mung bean showed higher egg shell thickness than those fed diet containing 10% raw mung bean. It was concluded that raw mung bean is a promising protein source that can be added up to 15% into laying hen diets contributing as much as 22.21% of the total dietary protein without negative effects on productive performance and egg quality of laying hen from 55 to 63 weeks of age.